European development cooperation : in between the local and the global - Hoebink, Paul (EADI., 2010)
"Official Development Assistance, or foreign aid, disbursed by the EU member states reached record levels in 2008, when several member states raised their assistance considerably and when some of the new member states became donors again. ... [This book] analyses a wide range of aspects of European development cooperation, covering, among others, some hotly debated issues such as the Economic Partnership Agreements, policy coherence and the participation of civil society organisations in negotiations with the European Union"--Page 4 of cover